Immunoregulatory soluble CTLA-4 modifies effector T-cell responses in systemic lupus erythematosus. Issue 1 (December 2016) - Dahal, Lekh; Basu, Neil; Youssef, Hazem; Khanolkar, Rahul; Barker, Robert; Erwig, Lars; Ward, Frank
Abstract Background The inhibitory CTLA-4 molecule is a crucial regulator of immune responses and a target for therapeutic intervention in both autoimmunity and cancer. In particular, CTLA-4 is important in controlling antigen-specific immunity, including responses to autoantigens associated with autoimmune disease. Here, we investigate cytokine responses to a range of lupus-associated autoantigens and assess whether the alternatively spliced isoform of CTLA-4, soluble CTLA-4 (sCTLA-4), contributes to immune regulation of autoantigen-specific immunity in systemic lupus erythematosus (SLE). Methods The cell culture supernatant production of sCTLA-4 as well as the cytokines IL-10, IFN-γ, and IL-17 from peripheral blood mononuclear cells (PBMC) from lupus patients and age- and sex-matched healthy volunteer donors were measured in response to previously identified histone and small nuclear ribonucleoprotein (snRNP) autoantigen-derived peptides (H391-105, H471-93, and U170K131-151 ) by ELISA. We also examined the functional contribution of sCTLA-4 to immune regulation in the context of these autoantigenic peptides following blockade of sCTLA-4 with a selective anti-sCTLA-4 monoclonal antibody, JMW-3B3. Results We identified responses to autoantigenic peptides, which revealed qualitative differences in cytokine (IL-10, IL-17, and IFN-γ) profiles between SLE patients and healthy donors. PBMC from healthy donors responded to each of the lupus peptides by secreting IFN-γ and IL-17, but PBMC from SLE patients produced IL-10. Although we did not observe differences in the levels of serum or PBMC culture supernatant sCTLA-4 in either cohort, blockade of sCTLA-4 in PBMC cultures responding to antigen enhanced the cytokine profiles associated with each group. Conclusion The results show that lupus autoantigen-derived peptides display varied immunogenicity in lupus versus healthy volunteer donors, while sCTLA-4 acts to regulate the T-cell activity independently of response profile.